Ascorbate-dependent and ascorbate-independent Mn porphyrin cytotoxicity: anticancer activity of Mn porphyrin-based SOD mimics through ascorbate-dependent and -independent routes - Bader Hasan; Artak Tovmasyan; Ines Batinic-Haberle; Ludmil Benov (Taylor & Francis Group, 2021)
Objective The aim of this study was to investigate how modifications at the periphery of the porphyrin ring affect the anticancer activity of Mn porphyrins (MnPs)-based SOD mimics. Methods Six compounds: MnTE-2-PyP with a short ethyl chain on the pyridyl ring; MnTnHexOE-2-PyP and MnTnOct-2-PyP with linear 8-atom alkyl chains, but the former with an oxygen atom within the alkyl chain; MnTE-2-PyPhP and MnTPhE-2-PyP with pyridyl and phenyl substituents, were investigated. Cytotoxicity was studied using pII and MDA-MB-231 cancer cell lines. Viability was assessed by the MTT (3-[4,5-dimethylthiazol-2-yl)]-2,5-diphenyltetrazolium bromide) assay and cell proliferation was determined by the sulforhodamine B assay. Results Cellular uptake was increased with the increase of the lipophilicity of the compounds, whereas reduction potential (E½) of the Mn(III)/Mn(II) redox couple shifted away from the optimal value for efficient redox cycling with ascorbate, necessary for ROS production. Amphiphilic MnPs, however, exerted anticancer activity by a mechanism not involving ROS. Conclusion Two different processes account for MnPs cytotoxicity. MnPs with appropriate E½ act via a ROS-dependent mechanism. Amphiphilic MnPs with suitable structure damage sensitive cellular constituents, leading to the suppression of proliferation and loss of viability. Design of compounds interacting directly with sensitive cellular targets is highly promising in the development of anticancer drugs with high selectivity and specificity.